Opmerkings oor die teologie van Psalm 106 - Oberholzer, J. P. (Hervormde teologiese studies, 1988)
Remarks on the theology of Psalm 106 A structural analysis of this liturgical song shows up the prayer for deliverance (vs 47) as focal point, cast against the background of the confession of guilt (vs 6), elaborated by reference to past history. Theologically the psalm is representative of what can be found on many pages of the Old Testament. A liturgy constructed around the history between God and man finds full richness in the contrast between divine and htmian acts and in the confession of the saving grace which gives life in spite of the contrast.